2017
DOI: 10.1007/s10490-017-9542-z
|View full text |Cite
|
Sign up to set email alerts
|

From LLL to IOL3: Moving dragon multinationals research forward

Abstract: In the past decade, there has been a large number of studies on how firms from the fast developing Asia-Pacific region initiate and manage their international business expansions, leading to an emerging area of research which could be labeled as dragon multinationals research. To illustrate how we can move dragon multinationals research forward, in this editorial we first expand John Mathews' linkage-leveragelearning (LLL) model to an extended framework of inward linkages-outward linkagesleverage-learning (IOL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Second, in line with a recent call for a more refined understanding of the home country institutional constraint of LLL framework (Lu et al 2017), our findings support the interaction effect of the country level characteristics, including economic distance and economic freedom, on EMFs' post-acquisition operating performance. While economic distance in general negatively impacts the EMF acquirers' postacquisition performance, the home emerging economy in transition in terms of its economic freedom presents significant challenges.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Second, in line with a recent call for a more refined understanding of the home country institutional constraint of LLL framework (Lu et al 2017), our findings support the interaction effect of the country level characteristics, including economic distance and economic freedom, on EMFs' post-acquisition operating performance. While economic distance in general negatively impacts the EMF acquirers' postacquisition performance, the home emerging economy in transition in terms of its economic freedom presents significant challenges.…”
Section: Discussionsupporting
confidence: 86%
“…A recent study on Chinese listed firms also suggests that older companies with more experience have the greater absorptive capacity, which results in a better position to overcome the cultural differences and enjoy better stock return after the acquisitions events (Li et al 2016). Likewise, Lu et al (2017) reviewed recent studies based on dragon multinationals and expanded LLL model to an extended framework of inward linkages-outward linkages-leverage-learning (IOL3) framework. Lu et al (2017) observed that beyond the outward linkages, established dragon multinationals also developed inward linkages within their home market, so they can garner home country resources which are instrumental in propelling EMFs' further internationalization.…”
Section: Economic Distance and Emfs' Post-acquisition Integrationmentioning
confidence: 99%
See 3 more Smart Citations